Ten ways to get a grip on designing and implementing a competency-based medical education training program - Hsu, Tina; De Angelis, Flávia; Al-Asaaed, Sohaib; Basi, Sanraj K; Tomiak, Anna; Grenier, Debjani; Hammad, Nazik; Henning , Jan-Willem; Berry, Scott; Song, Xinni; et al. (Canadian Medical Education Journal, 2021)
Background: Globally there is a move to adopt competency-based medical education (CBME) at all levels of the medical training system. Implementation of a complex intervention such as CBME represents a marked paradigm shift involving multiple stakeholders. Methods: This article aims to share tips, based on review of the available literature and the authors’ experiences, that may help educators implementing CBME to more easily navigate this major undertaking and avoid “black ice” pitfalls that educators may encounter. Results: Careful planning prior to, during and post implementation will help programs transition successfully to CBME. Involvement of key stakeholders, such as trainees, teaching faculty, residency training committee members, and the program administrator, prior to and throughout implementation of CBME is critical. Careful and selective choice of key design elements including Entrustable Professional Activities, assessments and appropriate use of direct observation will enhance successful uptake of CBME. Pilot testing may help engage faculty and learners and identify logistical issues that may hinder implementation. Academic advisors, use of curriculum maps, and identifying and leveraging local resources may help facilitate implementation. Planned evaluation of CBME is important to ensure choices made during the design and implementation of CBME result in the desired outcomes. Conclusion: Although the transition to CBME is challenging, successful implementation can be facilitated by careful design and strategic planning.